HUBUNGAN MEKANISME KOPING DENGAN KUALITAS HIDUP PADA PASIEN KANKER PAYUDARA - Wiwik Nurhikmah; Abdul Wakhid; Rosalina Rosalina (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2018)
THE ROLE OF MENTAL HEALTH CADRES IN THE HANDLING OF MENTAL PATIENTS ABSTRACTPatients with cancer have a very significant increase including breast cancer that causes death. Breast cancer affects the greatest impact on the sufferer, thus affecting the quality of life. Decreased quality of life that is not resolved will inhibit treatment that will cause death. The purpose of this study was to determine the relationship between coping mechanism with quality of life in breast cancer patients. This research design is descriptive correlational with cross sectional approach. The population of this study was breast cancer patients with a sample of 55 respondents using accidental sampling technique and data collection tool using Cancer Coping Questionnaire 21 and WHOQoL-BREF. Data analysis used chi square test. The results showed that the mechanism of coping cancer patients 65.5% adaptive category, quality of life of breast cancer patients bad category 52,7%. There is a relationship of coping mechanism with quality of life in breast cancer patients who underwent chemotherapy with p value 0,048 (α = 0,05). Should the hospital facilitate interaction activities with fellow breast cancer patients in order to share experiences about improving the quality of life. Keywords: Mechanism of Coping, Quality of Life, Breast Cancer Patients